EEG Brain Waves Pattern Analysis on the Specified Human Daily Activity - Nurul Hidayah, Saifuddin; Abdullah, Embong (2013)
This paper describes about EEG brain wave's pattern analysis related to human specific daily activities. EEG is a study of changing electric potential of the brain. As we know, brain is one of the most complex systems in the universe. This study proposes a simple way to analyze some EEG data due to human activities. It shows that there are distinct different brain waves pattern for different daily activities including sleeping, reading and music listening. Some of these activities will tire our bodies. This paper al-so gave brain waves pattern comparisons between tired brain and tired body